BrSQE1 and the ethylene signaling pathway suppress cell division to regulate plant size in Chinese cabbage (Brassica rapa subsp. pekinensis) - Yang, Rui; Wang, Qianyun; Ren, Yuhong; Li, Yongcheng; Wang, Jiajie; Feng, Daling; Ma, Wei; Li, Na; Yang, Lei; Zhao, Jianjun (Frontiers in Plant Science, 2025)
The heading leaves of Chinese cabbage (Brassica rapa L. ssp. pekinensis) represent a critical agronomic trait that serves as the primary economic organ in Chinese cabbage. Leaf morphogenesis, a complex developmental process, is fundamentally regulated by ethylene, a phytohormone with concentration-dependent effects on plant growth. It is known that high ethylene concentrations promote leaf elongation through cell expansion and that supraoptimal levels exert inhibitory effects on growth, but the underlying mechanisms remain unclear. In this study, a forward genetics approach was employed to elucidate the genetic and molecular bases of leaf size regulation using the small-leaf mutant mini35 and its wild-type counterpart A03. Through MutMap-based positional cloning, the causal gene was identified. Transcriptome profiling was conducted to analyze differentially expressed genes. Exogenous ethylene application (20–60 mg/L) was performed to evaluate its effects on leaf development. BrSQE1, encoding squalene epoxidase 1, as the causal gene localized to chromosome A09 through MutMap-based positional cloning. Transcriptome profiling revealed significant enrichment of differentially expressed genes in the ethylene signaling pathways. Exogenous ethylene application (20–60 mg/L) showed dose-dependent effects, with low concentrations primarily suppressing cell proliferation and higher concentrations inhibiting both cell division and expansion processes. Taken together, our findings elucidate the mechanism of ethylene-mediated leaf size regulation and provide valuable genetic resources for molecular breeding aimed at optimizing heading leaf formation in Brassica crops.